Impact of COVID-19 pneumonia on pulmonary vascular volume - Fahrni, Guillaume; Rocha, Ana-Carolina; Gudmundsson, Louis; Pozzessere, Chiara; Qanadli, Salah D.; Rotzinger, David C. (Frontiers in Medicine, 2023)
Background: Pulmonary manifestations of COVID-19 pneumonia are well known. However, COVID-19 is also associated with a range of vascular manifestations such as embolism, congestion, and perfusion changes. Regarding congestion, research from different groups has suggested arteriovenous anastomosis dysregulation as a contributing factor. In this study, we aim to better describe the changes in vascular volume in affected lung zones and to relate them to physiopathological hypotheses. Methods: We performed automatic vascular volume extraction in 10 chest CTs of patients, including 2 female and 8 male with a mean age of 63.5 ± 9.3 years, diagnosed with COVID-19 pneumonia. We compared the proportion of vascular volumes between manually segmented regions of lung parenchyma with and without signs of pneumonia. Results: The proportion of vascular volume was significantly higher in COVID (CVasc) compared to non-COVID (NCVasc) areas. We found a mean difference (DVasc) of 5% and a mean ratio (RVasc) of 3.7 between the two compartments (p < 0.01). Conclusion: Vascular volume in COVID-19 affected lung parenchyma is augmented relative to normal lung parenchyma, indicating venous congestion and supporting the hypothesis of pre-existing intra-pulmonary arteriovenous shunts.